The Outlaw Noble Salt : a novel - Harmon, Amy (Seattle : Lake Union Publishing, 2024)
"When infamous outlaw Butch Cassidy decides to go straight, he discovers that too many of the powerful men he crossed won't let bygones be bygones. To have a chance at a new life, he'll have to become someone else entirely. A brief, fateful encounter with the celebrated singer Jane Touissant on the eve of his escape offers a glimpse of what might have been, but Butch disappears, leaving her behind, until their paths unexpectedly converge again in Paris. Despite having discovered his true identity, Jane trusts the outlaw and enlists his protection on her upcoming American tour. Although Butch is reluctant to agree, fearing his sordid past may put the woman and her young son in danger, the salvation she offers is too hard to resist. As they set forth on their journey, Butch's past and Jane's secrets put them at risk from threats far greater than the law, and this legend of the American West will have to decide what matters most-his life, his legacy, or the woman he loves"--.
new book 2024 spring.
Keywords: Cassidy, Butch, -- 1866- -- Fiction; Outlaws -- Fiction; Women singers -- Fiction; Secrecy -- Fiction; Man-woman relationships -- Fiction; Women singers; Historical fiction; Romance fiction; Novels; Historical fiction; Romance fiction